EVALUASI MUTU DAN DAYA SIMPAN ROTI MANIS YANG DIBUAT MELALUI SUBSTITUSI TEPUNG TERIGU DENGAN PATI SAGU DAN MOCAF - Usman Pato; Fajar Restuhadi; Akhyar Ali; Rahmawati Ulfah; Mukmin ' (Jurnal Sagu, 2012)
Sago starch has been long used as a staple food for making traditional foods such askapurung, pepeda, sagu bakar etc. especially for people living in the eastern part of Indonesia.Nowadays there is also a novel flour called Mocaf (Modified cassava flour) made from cassava. Thepurpose of the present study was to find out the best formulation in production of sweet bread madefrom wheat flour substituted with sago starch and Mocaf. The research was done by using CompletelyRandomized Design with six treatments. Parameters observed were contents of moisture, ash, andstarch as well as leavening power of dough, gelatinous filament, self life and organoleptic assessmentof sweet bread. The data obtained were analyzed by ANOVA and was continued with DNMRT test at5% level. Meanwhile the organoleptic data were analyzed by Friedman Test and data of gelatinousfilament, flavor and rancidity were presented by descriptive analysis. Results showed that substitutionof sago starch and mocaf significantly affected the contents of moisture, ash and starch as well asleavening power of dough, however they did not influence the organoleptic assessment of sweet bread.The treatment of TSM3 was the best substitution formula which produced sweet bread that meets theIndonesian quality standard of sweet bread (SNI 01-3840-1995). The self life of sweet bread in thetreatment TSM3 (wheat flour 70%, 15% sago starch and 15% mocaf) and commercial sweet breadwas the same.